Effect of the Technology Acceptance Model on the Use of QRIS on The Financial Literacy Needs of Surakarta Klewer Market Traders - Pradianto, Mi’raj Akbar; Sangka, Khresna Bayu; Totalia, Salman Alfarisy (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
The spread of technology and the increasing number of internetiusers have significantly impacted society and individuals in the era of the fourth industrial revolution. This research aims to determine the influence of the technology acceptance model perspective (perception of usefulness, perception of ease of use), product knowledge, social influence on the financial literacy needs of Klewer Market traders in the city of Surakarta, using data collection techniques through questionnaires. Samples were taken using probability sampling, namely, proportionate stratified random sampling with a sample of 325 traders. The instrument validity test in this research used Pearson product moment and the instrument reliability test used Croanbach alpha. Research data analysis techniques use descriptive statistics, multiple regression analysis, and t-test analysis. The results of this research show that there is a significant influence between perceived usefulness ofiQRIS, perceived ease ofiuse of QRIS, knowledge of QRIS products, social influence on the financial literacy needs of Klewer Market traders in Surakarta city.